Linking Farmers and Agro-processors to the Tourism Industry in the Eastern Caribbean - Jansen, Hans; Stern, Adam; Weiss, Eli (World Bank, Washington, DC, 2016)
The main objective of this Economic and Sector Work (ESW) is to identify opportunities for stronger linkages between domestic agricultural supply chains and the tourism sector in the OECS, and to outline priority interventions with potential to strengthen these linkages. Since this topic has been analyzed in a number of studies, the approach for this ESW is not to conduct yet another comprehensive study. Instead, the goal is to validate and build on previous work through detailed field interviews with a selected sample of ‘game changers in the private and public sectors, and to come up with priority areas of focus and investments. The continued focus on strengthening the agriculture-tourism linkages is appropriate given the unexploited possibilities for increasing the share of locally sourced food purchased by the tourism sector and reducing the growing food import bill. The studies also identified specific types of food with potential to satisfy demand from the tourism sector. Both studies caution, however, that the potential for local production to replace imports is limited, given the regions agro-climatic conditions and price competitiveness. The World Bank, FAO study estimated that the scope to substitute tourism import demand by local produce is limited to around 11 percent of hotel food imports, equivalent to approximately 2 percent of the total food import bill. The study estimated that the annual ‘leakage of the tourism sector in fresh products could be reduced by about US$10 million, arguing that local and regional markets have greater potential to lower the food import bill.